JENIS-JENIS CAPUNG (Odonata:Anisoptera) DI KOMPLEK PERKANTORAN PEMERINTAH DAERAH (PEMDA) KABUPATEN ROKAN HULU - Herpina, Rima; Ade, Filza Yulina; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Dragonflies (Anisoptera) plays an important role for the sustainability of ecosystems. In an ecosystem, these insects serve as bio-indicators of the environment. This study aims to determine the species of dragonflies in Local Komplek Perkantoran Pemerintah Daerah Kabupaten Rokan Hulu. This study has been conducted on December 2014 with a survey method. Dragonflies are then identified by describing the types of dragonflies are obtained. Results of the study found 5 species including to 1 family and 4 genera with 17 individuals. As for the types of dragonflies obtained is Orthetrum sabina, O. chrysis, Pantala faverscens, Portamarcha congeners and Diplocoded trivialis